Endogeic earthworm densities increase in response to higher fine-root production in a forest exposed to elevated CO2. (July 2018) - Sánchez-de León, Yaniria; Wise, David H.; Lugo-Pérez, Javier; Norby, Richard J.; James, Samuel W.; Gonzalez-Meler, Miquel A.
Abstract: Net primary productivity (NPP) influences soil food webs and ultimately the amount of carbon (C) inputs in ecosystems. Earthworms can physically protect organic matter from rapid mineralization through the formation of soil aggregates. Previous studies at the Oak Ridge National Laboratory (ORNL) Free Air CO2 Enrichment (FACE) experiment showed that elevated [CO2 ] (e[CO2 ]) increased fine-root production and increased soil C through soil aggregation compared to ambient [CO2 ] (a[CO2 ]) conditions. Our first objective was to study the response of earthworms to increased leaf and root-litter inputs caused by increased atmospheric [CO2 ] exposure. We also took advantage of the CO2 shutdown at the ORNL FACE site to track the shift of the δ 13 C signal in leaf-litter, fine roots, earthworms, earthworm casts, and bulk soil. Densities of the most abundant endogeic earthworm, Diplocardia spp., were positively correlated with the previous-year production of leaf litter (r = 0.66, P = 0.02) and fine roots (r = 0.62, P = 0.03); and with the leaf-litter production (r = 0.63, P = 0.03) and fine-root production (r = 0.59, P = 0.05) two years before earthworms were sampled. Within two years after the CO2 fumigation ceased, the 13 C/ 12 C ratio increased in leaf litter (P = 0.01) and in fine roots (P = 0.05), showing an ecosystem legacy effect on soil C inputs. However, the C isotopic composition of soil, endogeic earthworms and casts had not changed the two years after the CO2 fumigation ended. The positive response of earthworms to increased root NPP, caused by elevated [CO2 ], is consistent with the increased soil aggregate formation and increased soil C at the ORNL FACE in the e[CO2 ] treatment. Highlights: Endogeic earthworm numerical density increased with elevated atmospheric CO2. Earthworms positively responded to increased NPP promoted by elevated CO2. Legacy effects of elevated atmospheric CO2 on root NPP can alter soil C inputs.